1986
DOI: 10.3181/00379727-183-42416
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan- and Collagen-Degrading Enzymes from Human Interleukin 1-Stimulated Chondrocytes from Several Species: Proteoglycanase and Collagenase Inhibitors as Potentially New Disease-Modifying Antiarthritic Agents

Abstract: Human IL-I -stimulated chondrocytes derived from rabbit, bovine, and human articular cartilage produce proteoglycan-and collagen-degrading enzymes. These studies demonstrate that the biological activity of IL-1 is not species specific. Several thiol, carboxyalkyl, and hydroxamic acid peptide inhibitors showed differential effects. The thiols were equipotent inhibitors of both the collagen-and proteoglycan-degrading enzymes whereas the carboxyalkyls appear to inhibit solely the proteoglycan-degrading enzyme(s).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
6
1
Order By: Relevance
“…This drug markedly inhibited these MMPs when tested at concentra- tions ranging from 10 -5 to 10 -9 M. Our findings are further supported by studies done by Caputo et al [9] in which rabbit articular cartilage derived proteoglycanase was also blocked in vitro by this drug at concentrations ranging from 10 -6 to 10 -8 M. Our IC 50 value of 1.8 × 10 -9 M for inhibition of MMPproteoglycanases was at least one order of magnitude lower than the previously reported IC 50 values of 6.0 × 10 -8 M [9] and 4.2 × 10 -6 M [16] of the same drug. In addition, studies from DiPasquale et al [16] have shown that U-24522 is approximately 10 times more potent against the proteoglycan-than the collagen-degrading enzymes derived from articular chondrocytes. Current theory suggests that the hydroxamic acid functional group chelates the zinc molecule at the active site of the MMPs thereby inactivating the enzyme [25].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This drug markedly inhibited these MMPs when tested at concentra- tions ranging from 10 -5 to 10 -9 M. Our findings are further supported by studies done by Caputo et al [9] in which rabbit articular cartilage derived proteoglycanase was also blocked in vitro by this drug at concentrations ranging from 10 -6 to 10 -8 M. Our IC 50 value of 1.8 × 10 -9 M for inhibition of MMPproteoglycanases was at least one order of magnitude lower than the previously reported IC 50 values of 6.0 × 10 -8 M [9] and 4.2 × 10 -6 M [16] of the same drug. In addition, studies from DiPasquale et al [16] have shown that U-24522 is approximately 10 times more potent against the proteoglycan-than the collagen-degrading enzymes derived from articular chondrocytes. Current theory suggests that the hydroxamic acid functional group chelates the zinc molecule at the active site of the MMPs thereby inactivating the enzyme [25].…”
Section: Discussioncontrasting
confidence: 73%
“…Hydroxamic acid derivates seem to be the most potent inhibitors of chondrocyte derived proteoglycanases and collagenases compared with carboxyalkyl peptides or thiol peptides [9,16]. We therefore investigated the effect of the hydroxamic acid derivate U-24522 on three aspects of chondrocyte metabolism which were in part modified by the drug: PG synthesis, PG release and activ- Table 3.…”
Section: Discussionmentioning
confidence: 98%
“…Preparation of the labeled samples, typically about 1 mM, and of the buffers (containing I O rnM Tris-dll-HCI, pH 7.0, 20 mM CaCI,, 15% acetonitrile43 and 8% D,O) was as described by . The hydroxamatesubstituted inhibitor (IC1 U24522; DiPasquale et al, 1986) was present at a ratio of 1: 1 with the protein for the half-filtered experiments (cf. Ikura .…”
Section: N M R Data Collection and Handlingmentioning
confidence: 99%
“…We present here the solution structure of human stromelysin's catalytic domain under conditions of higher calcium affinity (pH 7.0), and concentration, complexed with a hydroxamate inhibitor of more hydrophobic character ((R,S)-N-[2-[2-(hydroxamino)-2-oxoethyI]-4-methyl-l-oxopentyl]-~-leucyl-~-phenylalaninamide; DiPasquale et al, 1986) and in the presence of acetonitrile as a co-solvent. Our solution structure of the catalytic domain of human stromelysin reveals the binding mode of this peptide substrate analogue in the hydrophobic pockets of the active site (Kinemages 1 and 2) (Protein Data Bank access codes lUMT and IUMS).…”
mentioning
confidence: 99%
“…Most interestingly, the interaction of cells (cell products) associated with the inflammatory lesion (monocytes and T-cells) with synovial cells or chondrocytes can induce collagenase synthesis in these cells [12][13][14]. Interleukin-1 (IL-1), a macrophage or monocyte product, has been identified as a potent stimulator of collagenase synthesis [15][16][17][18][19]. Other agents such as T-cell products [14], uric acid crystals [20] and phorbol esters [21,22] have also been shown to stimulate connective tissue degrading activity by synovial cells, chondrocytes or cartilage.…”
Section: Introductionmentioning
confidence: 99%